Uncovering Undergraduates’ Innovative Talents towards Employment Generation for National Growth and Development: Implications of Integrating Entrepreneurship Education into Science Teacher Education Programmes in Rivers State - Dr. Inibehe Sunday Etokeren; Dr. Chinda Worokwu (Researchparks Publishing, 2022)
Innovative talents remain imperative for maximum and proper utilization of a nation's limited resources to attain insurmountable advancement in scientific and technological achievements. Ideally, Innovation is a basic need for national progress and sustainable development mostly in developing nations like Nigeria. It is tough for any country to survive in today’s competitive and digital world without innovations and creativity. This study therefore, aims at examining the implications of integrating entrepreneurship education into science teacher education programmes towards employment generation for national growth and development. The sample consisted of 311 science education undergraduates from Rivers State Tertiary institutions, and the survey was conducted using a descriptive survey technique. The study was guided by three research questions and two hypotheses. Two Science Education and one Measurement and Evaluation Lecturers validated a 15-item questionnaire titled